Suitability for e-health of non-pharmacological interventions in connective tissue diseases: scoping review with a descriptive analysis. Issue 2 (29th July 2021) - Ritschl, Valentin; Ferreira, Ricardo J O; Santos, Eduardo José Ferreira; Fernandes, Rúben; Juutila, Essi; Mosor, Erika; Santos-Costa, Paulo; Fligelstone, Kim; Schraven, Linda; Stummvoll, Georg; Salvador, Maria; Poole, Janet L; et al.
Abstract : Objective: Non-pharmacological interventions support patients with connective tissue diseases to better cope with and self-manage their diseases. This study aimed to map existing evidence on non-pharmacological interventions in patients with systemic lupus erythematosus (SLE), systemic sclerosis (SSc) and mixed connective tissue diseases regarding content, feasibility and potential suitability in an e-health setting. Methods: A literature search was performed in eight different databases in July 2020. The intervention's content was extracted using the 'Better reporting of interventions: template for intervention description and replication (TIDieR) checklist and guide'. A Sankey diagram and descriptive statistics were used to analyse the data and illustrate the relationships between the interventions. Results: Of 8198 identified records, 119 papers were eligible. One hundred and four of them (87.4%) were conducted between 2000 and 2020, mainly in the USA (SLE n=24 (21.2%), SSc n=16 (14.2%)), Brazil (SLE n=8 (7.1%), SSc n=5 (4.4%)) and Italy (SLE n=0 (0%), SSc n=12 (10.6%)). Fifty-two studies (SLE n=24 (21.2%), SSc n=28 (24.8%)) used multicomponent interventions. The single interventions were physical exercises (SLE n=16 (14.2%), SSc n=17 (15.0%)), coaching/counselling (SLE n=11 (18.0%), SSc n=0 (0%)) and education (SLE n=2 (1.8%), SSc n=3 (2.7%)). Primary outcomes focused on physical function (SLE n=1 (0.9%), SSc n=15 (13.3%)), mouth opening in SSc (n=4 (5.9%)) and physical capacity (SLE n=2 (1.8%), SSc n=1 (0.9%)). No interventions for mixed connective tissue disease were found. Conclusion: There was a great variety in the intervention's content due to differences in body structure, activity limitations and participation restrictions in SLE and SSc. These results highlight the need for personalised, multicomponent, non-pharmacological interventions, which could be delivered as e-health interventions.